Pengaruh pemanfaatan internet terhadap minat kunjung pemustaka ke Unit Pelaksana Teknis (UPT) Perpustakaan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Jelita, Elva; Raudhoh, Raudhoh; Miliani, Masyrisal (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
ABSTRACT Introduction. The purpose of this study was to determine whether there is an effect of internet use on student interest in visiting the UPT Library of the State Islamic University of Sulthan Thaha Saifuddin Jambi.. Data Collection Method. This research is a descriptive quantitative research with data collection techniques, namely observation, questionnaires and documentation. The population in this study were students who were active in the library of the State Islamic University of Sulthan Thaha Saifuddin Jambi. While the sample used the Slovin formula with accidental technique with a large sample of 99 people. Analysis Data.The data analysis technique is descriptive analysis, simple linear regression test, hypothesis testing and determination test. Results and Discussions. Based on the analysis of the percentage score on the internet utilization variable, it was obtained a score percentage of 81.46% in the 81.25% - 100% interval, which means that the use of the internet is included in the very good category. While the interest in visiting was obtained by a percentage score of 79.1% in the interval 62.50% - 81.24% which means that the interest in visiting is in the good category. Based on the simple linear regression test, there is an influence between internet use and visiting interest, the equation Y = 14.402 + 0.527 X is obtained, if every 1% increase in internet utilization rate (X) then visiting interest (Y) will increase by 0.527. Based on the hypothesis test, it is obtained that t count is 5.405 and a significant value of 0.00 then Ho is rejected and Ha is accepted. In the coefficient of determination, it is known that the R square value of 0.231 means that the effect of internet use (X) on visiting interest (Y) is 23.1% while 76.9% of visiting interest is influenced by other variables not studied. Conclusions. Based on the research that has been done, there is a strong relationship between internet use and visiting interest. . By using the internet, it makes communication easy for users, provides learning support in helping meet the information needs needed and utilizing the internet can help libraries in improving their services.